Prevalence of critical congenital heart defects and selected co‐occurring congenital anomalies, 2014–2018: A U.S. population‐based study. Issue 2 (19th January 2022) - Stallings, Erin Bugenske; Isenburg, Jennifer L.; Aggarwal, Deepa; Lupo, Philip J.; Oster, Matthew E.; Shephard, Hanna; Liberman, Rebecca F.; Kirby, Russell S.; Nestoridi, Eirini; Hansen, Brenda; Shan, Xiaoyi; Navarro Sanchez, Maria Luisa; et al.
Abstract: Background: Critical congenital heart defects (CCHDs) are one of the most common types of birth defects and can lead to significant morbidity and mortality along with surgical or catheter interventions within the first year of life. This report updates previously published estimates of CCHD prevalence with the latest population‐based surveillance data from 19 birth defect surveillance programs. Methods: The U.S. population‐based surveillance programs submitted data on identified cases of 12 CCHDs and co‐occurring cardiovascular and chromosomal birth defects from 2014 to 2018. We estimated prevalence by program type and maternal and infant characteristics. Among nine programs with active case ascertainment that collect more than live births, we estimated the percentage of co‐occurring cardiovascular and chromosomal birth defects for the 12 CCHDs. Results: We identified 18, 587 cases of CCHD among all participating programs. Overall CCHD prevalence was 19.6 per 10, 000 live births among all 19 programs and 20.2 per 10, 000 live births among active programs. Among maternal racial/ethnic groups, infants/fetuses born to American Indian/Alaska Native mothers showed the highest overall prevalence for all CCHDs (28.3 per 10, 000) along with eight of the 12 individual CCHDs. Among 7, 726 infants/fetuses with CCHD from active case ascertainment programs, 15.8% had at least one co‐occurring chromosomal birth defect. Conclusion: Our study provides prevalence estimates for CCHDs by maternal and infant characteristics along with co‐occurrence with cardiovascular and chromosomal birth defects among infants/fetuses with CCHD using one of the largest and most recent cohorts since the implementation of widespread CCHD screening. These data can provide a basis for future research to better understand risk factors for these defects.